Occlusion type and posterior communicating artery patency may predict favorable outcome after endovascular thrombectomy in selective basilar top occlusion - Park, Jung Soo; Im, Yong-Jin; Shin, Byoung-Soo; Kang, Hyun Goo (Frontiers in Neurology, 2022)
Introduction: The top of the basilar artery is a five-branched junction, consisting of two superior cerebellar arteries (SCAs), two posterior cerebellar arteries (PCAs), and the basilar artery itself. This study aimed to investigate prognostic factors in patients with selective acute basilar top occlusion managed with mechanical thrombectomy, focusing on occlusion type and posterior communicating artery (PCoA) patency. Methods: Eligible patients who underwent endovascular treatment (EVT) for acute basilar top occlusion were reviewed. Patterns of basilar top occlusion were categorized as types I–III according to whether the SCA and PCA were visible on angiography. The PCoA was categorized as hypoplastic or non-visible (type I), normal patency but non-visible PCA through PCoA flow (type II), and fetal type (type III). Results: Good outcomes were observed in 50% (21/42) and mortality in 11.9% (5/42) of the cases at 90 days. Patients with good outcomes showed lower baseline National Institutes of Health Stroke Scale (NIHSS) score (P=0.001) and a higher proportion of type III basilar top occlusion (P=0.004) and type III PCoA (P=0.001). Multivariable logistic analysis showed that baseline NIHSS score (odds ratio [OR], 0.84; 95% confidence interval [CI], 0.73–0.97; P=0.017) and type III PCoA (OR, 21.54, 95% CI, 1.33–347.97; P=0.031) were independent predictors of good functional outcomes. Conclusions: A low initial NIHSS score and good PCoA patency were independent predictors of favorable clinical outcomes after EVT in patients with acute basilar top occlusion. Furthermore, the favorable outcome group showed a high proportion of type III basilar top occlusions.